Feature. (November 2018) - Zhou, Jing; Chen, Jia; Goldsamt, Lloyd; Wang, Honghong; Zhang, Ci; Li, Xianhong
Abstract : N/A: Promoting HIV testing is an important strategy to end the HIV epidemic. HIV incidence among men who have sex with men (MSM) has increased rapidly in China in recent years, but HIV testing rates are still low. Our cross‐sectional study investigated HIV testing rates and analyzed associated factors in 565 MSM in Changsha between April and December 2014. In the previous year, 37.7% of participants had not been tested, 38.2% had had one test, and 24.1% had had two or more tests. Those who initiated sexual debut at an older age, had known someone infected with HIV, or had been diagnosed with a sexually transmitted illness (STI) were more likely to have had an HIV test. HIV intervention programs in China should focus on sexually active young MSM, integrate HIV testing and counseling services in STI clinics, and describe real experiences of living with HIV to improve HIV testing in MSM.